Community Health Status Indicators Project: The Development of a National Approach to Community Health - Marilyn Metzler, RN; Norma Kanarek, PhD; Keisher Highsmith, DrPH; Ron Bialek, MPP; Roger Straw, PhD; Ione Auston, MLS; Jennifer Stanley, MA; Richard Klein, MPH (Centers for Disease Control and Prevention, 2008)
The Community Health Status Indicators Project (CHSI) 2008 provides 16-page reports for the 3141 counties in the United States, each of which includes more than 300 county-specific data items related to chronic and infectious diseases, birth characteristics or outcomes, causes of death, environmental health, availability of health services, behavioral risk factors, health-related quality of life, vulnerable populations, summary measures of health, and health disparities. The CHSI, originally initiated in 2000, provides county-level health profiles for all U.S. counties so that programs addressing community health can readily access community health indicators. Each county report also permits comparisons of a county's health status with similar "peer counties," with all counties, and with national Healthy People 2010 objectives. Under the leadership of a public-private partnership, the CHSI Steering Committee updated each county report and added new information and features to create CHSI 2008. This new CHSI version includes data for 1994 through 2006 from multiple surveillance systems. New features include an enhanced Web site, an Internet mapping application, and a downloadable database of the indicators for all counties.